B-ALL With t(5;14)(q31;q32); IGH-IL3 Rearrangement and Eosinophilia: A Comprehensive Analysis of a Peculiar IGH-Rearranged B-ALL - Fournier, Benjamin; Balducci, Estelle; Duployez, Nicolas; Clappier, Emmanuelle; Cuccuini, Wendy; Arfeuille, Chloé; Caye-Eude, Aurélie; Delabesse, Eric; Bottollier-Lemallaz Colomb, Elodie; Nebral, Karin; Chrétien, Marie-Lorraine; Derrieux, Coralie; et al. (Frontiers in Oncology, 2019)
Background: B-cell acute lymphoblastic leukemia associated with t(5;14)(q31;q32);IGH-IL3 is an exceptional cause of eosinophilia. The IGH enhancer on 14q32 is juxtaposed to the IL3 gene on 5q31, leading to interleukin-3 overproduction and release of mature eosinophils in the blood. Clinical, biological and outcome data are extremely scarce in the literature. Except for eosinophilia, no relevant common feature has been highlighted in these patients. However, it has been classified as a distinct entity in the World Health Organization classification. Cases presentation: Eight patients with t(5;14)(q31;q32) treated by French or Austrian protocols were retrospectively enrolled. Array comparative genomic hybridization, multiplex ligation-dependent probe amplification or genomic PCR search for IKZF1 deletion were performed in 7. Sixteen patients found through an exhaustive search in the literature were also analyzed. For those 24 patients, median age at diagnosis is 14.3 years with a male predominance (male to female ratio = 5). Eosinophilia-related symptoms are common (neurologic in 26%, thromboembolic in 26% or pulmonary in 50%). Median white blood cells count is high (72x109/L) and linked to eosinophilia (median: 32x109/L). Peripheral blasts are present at a low level or absent (median: 0x109/L; range: 0-37x109/L). Bone marrow morphology is marked by a low blast infiltration (median: 42%). We found an IKZF1 deletion in 5 out of 7 analyzable patients Outcome data are available for 14 patients (median follow-up: 28 months): 8 died and 6 are alive in complete remission. Some of these features are concordant with the ones seen of patients with other IGH-rearranged B-cell acute lymphoblastic leukemias: young age at onset, male sex, low blast count, high incidence of IKZF1 deletion and intermediate prognosis. Conclusion: Based on shared epidemiological and biological features, B-cell acute lymphoblastic leukemia with t(5;14)(q31;q32) is a peculiar subset of IGH-rearranged B-cell acute lymphoblastic leukemia with an intermediate prognosis and particular clinical features related to eosinophilia.